1993
DOI: 10.1002/ange.19931050238
|View full text |Cite
|
Sign up to set email alerts
|

Ein Hämerythrin‐Modellkomplex mit Katalaseaktivität

Abstract: Die katalytische Zersetzung von H2O2 zu O2 und H2O gelingt mit dem asymmetrischen Hämerythrinmodellkomplex 1, der eine labile Koordinationsstelle hat. Beim Katalysecyclus wird die Oxyhämerythrinform mit koordiniertem Hydroperoxidoliganden durchlaufen. L = 1,4,7‐Trimethyl‐1,4,7‐triazacyclononan, bpy= 2,2′‐Bipyridin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Disproportionation of H 2 O 2 into O 2 and H 2 O has been reported to occur upon reaction of H 2 O 2 with a synthetic Hr model complex. 18 We found that the met-WT reacted with H 2 O 2 within 10 min with a concomitant evolution of O 2 , which was confirmed by gas chromatography (Fig. S4, ESI † ).…”
supporting
confidence: 61%
“…Disproportionation of H 2 O 2 into O 2 and H 2 O has been reported to occur upon reaction of H 2 O 2 with a synthetic Hr model complex. 18 We found that the met-WT reacted with H 2 O 2 within 10 min with a concomitant evolution of O 2 , which was confirmed by gas chromatography (Fig. S4, ESI † ).…”
supporting
confidence: 61%
“…Several porphyrin-based Fe III complexes and Fe(II/III) complexes of non-heme ligands have been prepared in the past and claimed to be catalase mimics. However, none of these compounds satisfies the above definition in all aspects. ,,,, …”
Section: Discussionmentioning
confidence: 99%